(untitled) (Research, Society and Development, 2022)
The present study aims to analyze the consequences of drug consumption in the family context. The methodology used to conduct the study is based on a broad bibliographic investigation using articles, books, and magazines. The research was also a qualitative study, with a descriptive and explanatory approach. It was necessary to carry out a field study containing six (06) subjective questions directed to one (01) social worker. Besides the application of a form containing ten (10) subjective questions directed to seven (07) users assisted by CAPS AD. It was observed that the use of drugs often harms the user in social aspects, health, being physical or mental, and that the biggest difficulty between users and their families is the opportunity to have a conversation, a dialogue, because there is not the habit inserted in their living, although dialogue is something important for the addict to clarify their doubts and questions, and that family members come to teach through conversation the way of good and the way of evil. Finally, according to what has been proposed, it is hoped that the results found in this study will contribute to expand the existing knowledge in the area, encouraging further research.